Extra service sirn ; Black beauty ; Divine inspiration [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Tackles massage parlors in Metro Manila offering hospitality girl service; black Amerasians; and interview with Fr. Manoling Francisco about his composition being sung in Eucharistic celebrations.
Extra service, sirn (20 min.) -- Black beauty (15 min.) -- Divine inspiration (15 min.)
VHS.
Reporter, David Celdran.
Keywords: Francisco, Manoling -- Interviews; Baths, Vapor -- Philippines -- Manila; Sauna -- Philippines -- Manila; Musicians -- Philippines; Asian Americans -- Philippines